2022
DOI: 10.3389/fvets.2022.937991
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Disorder of Sexual Development in a Chinese Crested Dog With XX/XY Leukocyte Chimerism and Mixed Cell Testicular Tumors

Abstract: A 10-year-old intact female Chinese Crested dog was presented for evaluation and further diagnostics due to persistent symptoms of vulvar swelling, vaginal discharge, and an 8-year history of acyclicity. At presentation, generalized hyperpigmentation and truncal alopecia were identified, with no aberrations of the female phenotype. Vaginal cytology confirmed the influence of estrogen at multiple veterinary visits, and hormonal screening of progesterone and anti-Mullerian hormone indicated gonadal presence. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Herndon et al (2012) described a phenotypically female dog with testicles retained in the groin region, one of which was affected by a Sertoli cell tumor [11]. Moreover, different cases of persistence of the Mullerian duct and testicular tumors, have been described [19,20], and recently, Schwartz et al reported a phenotypically female DSD dog with XX/XY leukocyte chimerism and testicular mixed tumors [21]. Only few cases of DSD with neoplasms have been described in dogs, and this is probably due to premature castration, which reduces the probability of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Herndon et al (2012) described a phenotypically female dog with testicles retained in the groin region, one of which was affected by a Sertoli cell tumor [11]. Moreover, different cases of persistence of the Mullerian duct and testicular tumors, have been described [19,20], and recently, Schwartz et al reported a phenotypically female DSD dog with XX/XY leukocyte chimerism and testicular mixed tumors [21]. Only few cases of DSD with neoplasms have been described in dogs, and this is probably due to premature castration, which reduces the probability of tumor development.…”
Section: Discussionmentioning
confidence: 99%